A structured framework for improving outbreak investigation audits - Durrheim David N; Merritt Tony D; Dalton Craig B; Munnoch Sally A; Kirk Martyn D (BMC, 2009)
Abstract Background Outbreak investigation is a core function of public health agencies. Suboptimal outbreak investigation endangers both public health and agency reputations. While audits of clinical medical and nursing practice are conducted as part of continuous quality improvement, public health agencies rarely make systematic use of structured audits to ensure best practice for outbreak responses, and there is limited guidance or policy to guide outbreak audit. Methods A framework for prioritising which outbreak investigations to audit, an approach for conducting a successful audit, and a template for audit trigger questions was developed and trialled in four foodborne outbreaks and a respiratory disease outbreak in Australia. Results The following issues were identified across several structured audits: the need for clear definitions of roles and responsibilities both within and between agencies, improved communication between agencies and with external stakeholders involved in outbreaks, and the need for development of performance standards in outbreak investigations - particularly in relation to timeliness of response. Participants considered the audit process and methodology to be clear, useful, and non-threatening. Most audits can be conducted within two to three hours, however, some participants felt this limited the scope of the audit. Conclusion The framework was acceptable to participants, provided an opportunity for clarifying perceptions and enhancing partnership approaches, and provided useful recommendations for approaching future outbreaks. Future challenges include incorporating feedback from broader stakeholder groups, for example those of affected cases, institutions and businesses; assessing the quality of a specific audit; developing training for both participants and facilitators; and building a central capacity to support jurisdictions embarking on an audit. The incorporation of measurable performance criteria or sharing of benchmark performance criteria will assist in the standardisation of outbreak investigation audit and further quality improvement.